2012
DOI: 10.1158/1078-0432.ccr-11-1699
|View full text |Cite
|
Sign up to set email alerts
|

MiR-1 Downregulation Cooperates with MACC1 in Promoting MET Overexpression in Human Colon Cancer

Abstract: Purpose: MET, the tyrosine kinase receptor for hepatocyte growth factor, is frequently overexpressed in colon cancers with high metastatic tendency. We aimed to evaluate the role of its negative regulators, miR-1 and miR-199a à , and its transcriptional activator, the metastasis-associated in colon cancer 1 (MACC1), in controlling MET expression in human colon cancer samples.Experimental Design: The expression of MET, miR-1, miR-199a à , and MACC1 was evaluated by realtime PCR in 52 matched pairs of colorectal… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(70 citation statements)
references
References 54 publications
(49 reference statements)
3
66
0
1
Order By: Relevance
“…The MET oncogene encodes a tyrosine kinase receptor that binds hepatocyte growth factor (HGF) and drives the malignant progression of several tumour types (Reid et al 2012). Experiments in CRC cells have confirmed the tumour-suppressive ability of miR-1, as enforced expression impairs cell scattering, migration, wound-healing and proliferation in response to HGF (Migliore et al 2012). Thus, activation of MET, due to a decrease in miR-1 is likely to be associated to cancer progression and to the acquisition of an invasive phenotype and metastatic dissemination (Migliore et al 2012, Reid et al 2012.…”
Section: Global Mirna Profiling Reveals a Signature Specific For Smalmentioning
confidence: 99%
See 2 more Smart Citations
“…The MET oncogene encodes a tyrosine kinase receptor that binds hepatocyte growth factor (HGF) and drives the malignant progression of several tumour types (Reid et al 2012). Experiments in CRC cells have confirmed the tumour-suppressive ability of miR-1, as enforced expression impairs cell scattering, migration, wound-healing and proliferation in response to HGF (Migliore et al 2012). Thus, activation of MET, due to a decrease in miR-1 is likely to be associated to cancer progression and to the acquisition of an invasive phenotype and metastatic dissemination (Migliore et al 2012, Reid et al 2012.…”
Section: Global Mirna Profiling Reveals a Signature Specific For Smalmentioning
confidence: 99%
“…Experiments in CRC cells have confirmed the tumour-suppressive ability of miR-1, as enforced expression impairs cell scattering, migration, wound-healing and proliferation in response to HGF (Migliore et al 2012). Thus, activation of MET, due to a decrease in miR-1 is likely to be associated to cancer progression and to the acquisition of an invasive phenotype and metastatic dissemination (Migliore et al 2012, Reid et al 2012. Interestingly, our bioinformatic analyses revealed HGF to also be targeted by miR-1 and we found HGF levels significantly increased in LN and liver metastases compared with primary SBNETs (Supplementary Fig.…”
Section: Global Mirna Profiling Reveals a Signature Specific For Smalmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical data show that MET overexpression, in the absence of gene amplifi cation, is the most frequent cause of constitutive MET activation in human tumors and often correlates with poor prognosis. Overexpression can be caused by several factors, such as hypoxia ( 19 ), activation of upstream oncogenes ( 20,21 ), inactivation of tumor suppressor genes ( 22 ), or loss of miRNAs ( 23,24 ). MET gene amplifi cation, which drives increased expression and constitutive receptor activation, has been described in selected histotypes such as gastroesophageal, colorectal, endometrial, and lung carcinomas, glioblastomas, and medulloblastomas (reviewed in ref.…”
Section: Met/hgf and Cancermentioning
confidence: 99%
“…Metastasis-associated in colon cancer-1 (MACC1) has been reported to promote tumor proliferation and invasion mediated via hepatocyte growth factor (HGF)/ mesenchymal-epithelial transition factor (c-Met) signaling in colorectal cancer (Stein et al, 2009;Galimi et al, 2011;Migliore et al, 2012). Recently, a clinical study showed that aberrant overexpression of MACC1 may indicate poor prognosis of ovarian cancer patients for early recurrence and distance metastasis (Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%